2018
DOI: 10.1074/jbc.ra117.000441
|View full text |Cite
|
Sign up to set email alerts
|

Full-length amyloid precursor protein regulates lipoprotein metabolism and amyloid-β clearance in human astrocytes

Abstract: Mounting evidence suggests that alterations in cholesterol homeostasis are involved in Alzheimer's disease (AD) pathogenesis. Amyloid precursor protein (APP) or multiple fragments generated by proteolytic processing of APP have previously been implicated in the regulation of cholesterol metabolism. However, the physiological function of APP in regulating lipoprotein homeostasis in astrocytes, which are responsible for cholesterol biosynthesis and regulation in the brain, remains unclear. To address this, here … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
56
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 57 publications
(58 citation statements)
references
References 78 publications
2
56
0
Order By: Relevance
“…Interestingly, in these APP null neurons, simvastatin still reduced pThr231Tau/tTau in a dose-dependent manner identical to that of its isogenic control lines (Figure 3H). Similarly, simvastatin reduced pThr231Tau/tTau the same in a previously generated isogenic set of NDC (APP wt ) and APP null neurons (CV line 151 and IB6) (Fong et al., 2018) (Figure 3H). Together, these data show that CE regulate both pTau and Aβ, but regulation of pTau by CE is APP- and Aβ-independent.…”
Section: Resultssupporting
confidence: 62%
“…Interestingly, in these APP null neurons, simvastatin still reduced pThr231Tau/tTau in a dose-dependent manner identical to that of its isogenic control lines (Figure 3H). Similarly, simvastatin reduced pThr231Tau/tTau the same in a previously generated isogenic set of NDC (APP wt ) and APP null neurons (CV line 151 and IB6) (Fong et al., 2018) (Figure 3H). Together, these data show that CE regulate both pTau and Aβ, but regulation of pTau by CE is APP- and Aβ-independent.…”
Section: Resultssupporting
confidence: 62%
“…For astrocytic differentiation, we also followed a protocol previously reported 67 . Briefly, NPCs derived from hiPSC1/4/5/8 were seeded in a 10-cm plate and grown in NPC media containing 20 ng/mL of bFGF (Millipore; GF003AF-MG) to confluency, scraped, and transferred to three uncoated wells of a 6-well plate.…”
Section: Generation Of Hipsc-derived Npcs Neurons or Astrocytesmentioning
confidence: 99%
“…VEGF is a highly biologically active vascular growth promoting factor with neurotrophic, neuroprotective and angiogenic effects ( 25 ). It has been reported ( 26 ) that VEGF and β amyloid protein can promote each other in patients with AD, and β amyloid deposition is the main cause of the degeneration and death of peripheral neurons of senile plaques. The study by Mateo et al ( 27 ) demonstrated that VEGF expression in the serum of patients with AD was significantly decreased, while the study by Kakinuma et al ( 28 ) demonstrated that donepezil promoted cardiovascular growth and VEGF expression in mice.…”
Section: Discussionmentioning
confidence: 99%